2022
DOI: 10.2147/oajc.s329045
|View full text |Cite
|
Sign up to set email alerts
|

Modern Contraceptive Methods Predict Hemoglobin Levels Among Women of Childbearing Age from DHS 2016

Abstract: Objective This study aimed to study the association of different modern contraceptive methods and anemia on women of childbearing age. Methods The study was conducted based on secondary data from Ethiopia demographic and health surveys (EDHS) in 2016. The study included 12,981, women of childbearing age. The dependent variable is anemia which was defined based on the level of hemoglobin concentration, and was classified as non-anemic (above 12 g/dL) or anemic (below 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
3
4
0
1
Order By: Relevance
“…This was in agreement with a case-control study conducted in West Ethiopia that reported higher odds of anemia among pregnant women with a MUAC of less than 23 cm (AOR = 3.42; 95% CI: 2.07, 5.63) [27]. Malnutrition during pregnancy may be caused by poor dietary intake [4], low pre-pregnancy BMI (< 18.5 kg/m 2 ) [28], accompanied by infections and infestations, which is common in LMICs [29].…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with a case-control study conducted in West Ethiopia that reported higher odds of anemia among pregnant women with a MUAC of less than 23 cm (AOR = 3.42; 95% CI: 2.07, 5.63) [27]. Malnutrition during pregnancy may be caused by poor dietary intake [4], low pre-pregnancy BMI (< 18.5 kg/m 2 ) [28], accompanied by infections and infestations, which is common in LMICs [29].…”
Section: Discussionsupporting
confidence: 92%
“…22 Similarly, another study's result demonstrated the likelihood of anemia was decreased by around 40% as opposed to those who practiced the barrier method of contraception (OR=0.6,95% CI: 0.45 to 1.12). 23 While mentioning parity, multiparous females were found to have reduced serum ferritin levels (and hence low hemoglobin) as compared to the controls, indicating that multiple pregnancies do play a role in the context of the iron content inside the body. 24 Likewise, our study also had similar findings that the prevalence of anemia and iron deficiency was more among multiparous females as compared to nulliparous females.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, progesterone increases appetite and results in faster metabolism, while estrogen facilitates lipid metabolism and fat accumulation in the adipose tissue in the cell [ 22 ]. On the contrary, using those modern contraceptive methods; especially hormonal contraceptives had a high potential to improve the hemoglobin level among women of childbearing age [ 66 ]. Because of this paradoxical effect among modern contraceptive users, the co-occurrence of overweight/obesity and anemia is less likely to develop than for non-users and those on traditional methods.…”
Section: Discussionmentioning
confidence: 99%